2019
DOI: 10.1177/0969733019846645
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nurses’ duty to care and willingness to report

Abstract: Background: Nurses must balance their perceived duty to care against their perceived risk of harm to determine their willingness to report during disaster events, potentially creating an ethical dilemma and impacting patient care. Research aim: The purpose of this study was to investigate nurses’ perceived duty to care and whether there were differences in willingness to respond during disaster events based on perceived levels of duty to care. Research design: A cross-sectional survey research design was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…With the presence of a pandemic, staff nurses are stretched thin due to the lack of staff, which is why recruiting volunteers, especially nursing students, is recommended to overcome this problem (Blackwood, 2017;Hayter & Jackson, 2020;Iserson, 2020;McNeill et al, 2020;Swift et al, 2020;Quisao et al, 2021). However, from previous research, it can be observed that obtaining volunteers during an emergency can indeed be a challenge (Blackwood, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the presence of a pandemic, staff nurses are stretched thin due to the lack of staff, which is why recruiting volunteers, especially nursing students, is recommended to overcome this problem (Blackwood, 2017;Hayter & Jackson, 2020;Iserson, 2020;McNeill et al, 2020;Swift et al, 2020;Quisao et al, 2021). However, from previous research, it can be observed that obtaining volunteers during an emergency can indeed be a challenge (Blackwood, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although registered nurses are important healthcare providers, given their ability to offer direct care and support services, there is usually a nursing shortage (Blackwood, 2017). Disasters such as disease pandemics make nursing shortages more critical as such disasters increase patient demand, often exceeding the operational capacity of healthcare facilities (Blackwood, 2017;McNeill et al, 2020).…”
mentioning
confidence: 99%
“…Nurses also work within high stress environments and some too, are faced with the effects of a natural disaster event. The work of nurses who choose to volunteer when disasters affect their country or region has been explored in several studies across the globe (Ganz et al 2019;McNeill et al 2019;Nash 2017) and some, as is the case with this study, were caught up by chance in a disaster that affected their healthcare facility. Yet, the collective willingness and duty to care was one core characteristic that was evidenced strongly in the interview data.…”
Section: Discussionmentioning
confidence: 99%
“…Participants responded to questions regarding sociodemographic characteristics referring to previous studies: [15][16][17] age, marital status, religion, gender, education level, job position, working department, monthly income, and the type of hospital (size of hospital, type of department, severity of patients treated). Based on Jang, [18] who revised and supplemented Benner's [19] model according to the Korean population, careers were classified into 4 stages: the beginner level (up to 1 year of experience), advanced beginner level (more than 1 year and less than 3 years of experience), the competent level (more than 3 years and less than 7 years of experience), and the proficient level (7 years or more of experience).…”
Section: Instrumentsmentioning
confidence: 99%